The Influence of E-WoM, Social Media Marketing, Beauty Vlogger, and Endorser Congruence on Perfume Product Purchase Decisions Among Gen Z And Millennials - Maisal Ardi Maulana; Muhammad Arifiyanto (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
Perfume product purchases made by members of Generation Z and Millennials are investigated in this study, along with the elements that influence these generations opinions of E-WOM, beauty vloggers, social media marketing, and endorser congruence. We used a quantitative method by surveying 200 people from Generation Z and Millennials who had bought scent goods. . According to the findings, there is a favorable relationship between purchase decisions and E-WOM, social media marketing, beauty vloggers, and endorser congruence. Findings from this research stress the significance of influencer marketing and digital marketing in molding customer views and motivating purchases. The results give light on how perfume companies may enhance the efficacy of their digital marketing campaigns, especially in the realms of social media and influencer partnerships, to sway customer decision-making and boost sales.